2013
DOI: 10.1093/mp/sss081
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Nested Long Terminal Repeat Retrotransposons in Brassica Species

Abstract: Long terminal repeat (LTR) retrotransposons, one of the foremost types of transposons, continually change or modify gene function and reorganize the genome through bursts of dramatic proliferation. Many LTR-TEs preferentially insert within other LTR-TEs, but the cause and evolutionary significance of these nested LTR-TEs are not well understood. In this study, a total of 1.52Gb of Brassica sequence containing 2020 bacterial artificial chromosomes (BACs) was scanned, and six bacterial artificial chromosome (BAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 77 publications
(71 reference statements)
2
21
0
Order By: Relevance
“…Distribution patterns are associated with their function. For example, some LTR retrotransposable elements preferentially insert within other LTR retrotransposons in centromere regions, and these elements are rapidly duplicated, inserted repeatedly, and play a role in the formation of centromeres [47]. In the present study, FISH results revealed that most of the hybridization signals are preferentially concentrated in pericentromeric and distal regions of chromosomes (Fig.…”
Section: Chromosomal Localization Of Ltr Retrotransposonssupporting
confidence: 60%
See 1 more Smart Citation
“…Distribution patterns are associated with their function. For example, some LTR retrotransposable elements preferentially insert within other LTR retrotransposons in centromere regions, and these elements are rapidly duplicated, inserted repeatedly, and play a role in the formation of centromeres [47]. In the present study, FISH results revealed that most of the hybridization signals are preferentially concentrated in pericentromeric and distal regions of chromosomes (Fig.…”
Section: Chromosomal Localization Of Ltr Retrotransposonssupporting
confidence: 60%
“…The distribution bias, where TEs are preferentially inserted into the heterochromatin regions, might be beneficial for the retrotransposable elements facilitating escape from negative selection that arises from insertion into genes rich regions [54,55]. Additionally, LTR retrotransposable elements found in centromeres of various plant species have also been shown to contribute to the formation and function of centromeres [47,55]. Hence, our future studies will focus on the potential roles of these elements in centromere function.…”
Section: Chromosomal Localization Of Ltr Retrotransposonsmentioning
confidence: 99%
“…It was shown that LTR retrotransposons are more frequent in pericentromeric regions of the host genomes (for a review see Li et al 2013) and that they could play important roles in maintaining chromatin structures and centromere functions (Zhao and Ma 2013), or reshuffling the structure of the centromeric sequences (Wei et al 2013). In wheat, a Cereba-like element called centromeric retrotransposon in wheat (CRW) represents the main component of the centromeres .…”
Section: Retrotransposons Associate With Reduced Recombination Ratementioning
confidence: 99%
“…Such structures are known to be formed by the preferential insertion of an LTR-retrotransposon into pre-existing retrotransposons, creating large heterochromatic blocks [79,80]. Other than their potential role in centromere formation [91], and a negative influence on genome expansion [92], the cause and evolutionary significance of such structures largely remains unknown. …”
Section: Discussionmentioning
confidence: 99%